Faktor-faktor Penentu Resesi di Indonesia (Determinants of Recession in Indonesia) - Tria Apriliana (Universitas Batanghari Jambi, 2023)
The Covid-19 pandemic has had a further impact on the global economy, such as the threat of a recession. The Indonesian economy is making various efforts to be able to overcome the existing problems. This study aims to determine the determinants of recession in Indonesia. This research uses a secondary database from the Central Statistics Agency, Bank Indonesia, Bank Indonesia and the World Bank for the period March 2020 to September 2022. (The Covid-19 pandemic has entered Indonesia until now). The analytical method used in this research is Ordinary Least Squared (OLS). The results of this study indicate that there are four variables that have a significant effect on economic growth, namely inflation, domestic interest rates, world crude oil prices, and exchange rates. The variables that have the most influence on changes in economic growth are the rupiah exchange rate against the dollar, then domestic interest rates, then inflation and finally world crude oil prices.